UNDERSTANDING EXPERIENCES WITH INTERPROFESSIONAL COLLABORATION AMONG NURSES, PARAMEDICS, AND PHYSICIANS IN SAUDI EMERGENCY DEPARTMENTS: A QUALITATIVE STUDY - Thamer Musa Ahmed Alanazi, Ahmed Mohammed Ahmed Alatmi, Nawwaf Mownas Alanazi, Tahani Mohammed Ahmed Alatmi, Hanan Mohammed Ahmed Alatmi, Abdulrahman Manaa Saad Almutairi (Chelonian Research Foundation, 2022)
Effective interprofessional collaboration among healthcare professionals is vital for delivering coordinated, safe, high-quality care, especially in chaotic emergency department (ED) settings. However, minimal research exists elucidating the state of interprofessional collaboration between key ED providers in Saudi Arabia. This qualitative study aimed to address this gap by conducting semi-structured interviews with 15 emergency nurses, 15 paramedics, and 15 emergency medicine physicians regarding perspectives and experiences with interprofessional collaboration in two urban Saudi EDs. Transcripts underwent inductive thematic analysis. Several key themes emerged, including perceived benefits of collaboration coupled with inconsistencies in practice, role ambiguity between nurses and paramedics that hindered cooperation, the existence of professional hierarchies affecting team dynamics, the need for a shared mental model when providing urgent care, and influences of the high-pressure ED environment on collaborative interactions. Participants emphasized the importance of interprofessional education initiatives, open and egalitarian communication channels, implementation of structured team training programs, flattening of professional hierarchies, and establishment of protocols to enhance collaboration. Study findings provide important insights that can inform tailored organizational and educational strategies aimed at optimizing interprofessional collaboration among ED providers in Saudi Arabia to enhance delivery of coordinated, team-based emergency care.